Reliability and validity of the Chinese version of the sunlight exposure questionnaire - Xiaoxia Wang; Qin Wang; Qin Wang; Zhe Li; Zhe Li; Mengjie Chen; Maoting Guo; Laixi Kong; Liyuan Chen; Xiaolong Li; Junjun Li; Qieyan Cao; et al. (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to translate and validate the reliability and validity of the Chinese version of the Philippines Sunlight Exposure Questionnaire.MethodsA total of 392 Chinese individuals aged at least 18 years, residing in various cities in Sichuan province for at least 1 year, were recruited. The reliability of the Chinese version of the questionnaire was measured through internal consistency, split-half reliability, and retest reliability, while validity was determined using the content validity index and the structure validity index.ResultsThe Chinese version of the Sunlight Exposure Questionnaire, which includes 19 items covering 5 factors, demonstrated McDonald's omega coefficient of 0.788. The split-half reliability of the questionnaire was 0.823, and the retest reliability was 0.940. The content validity index (S-CVI) was 0.952. The five-factor structure, supported by eigenvalues, explained 66.2% of the total variance. Confirmatory factor analysis indicated favorable model fit.ResultsThe chi-square value degrees of freedom ratio (χ2/df) = 1.852, the goodness-of-fit index (GFI) = 0.938, the normed fit index (NFI) = 0.922, the incremental fit index (IFI) = 0.962, the comparative fit index (CFI) = 0.962, the Tucker-Lewis index (TLI) = 0.952, and root mean square error of approximation (RMSEA) = 0.047. The indicators of the fit of the model were within reasonable bounds.ConclusionThe Chinese version of the Sunlight Exposure Questionnaire shows validity and good reliability for assessing sun exposure among adults in a Chinese cultural context.